Cocaine-Induced Changes in Low-Dimensional Attractors of Local Field Potentials in Optogenetic Mice - Oprisan, Sorinel A.; Imperatore, Julia; Helms, Jessica; Tompa, Tamas; Lavin, Antonieta (Frontiers in Computational Neuroscience, 2018)
Optogenetically evoked local field potential (LFP) recorded from the medial prefrontal cortex (mPFC) of mice during basal conditions and following a systemic cocaine administration were analyzed. Blue light stimuli were delivered to mPFC through a fiber optic every 2 and each trial was repeated 100 times. As in the previous study, we used a surrogate data method to check that nonlinearity is present in the experimental LFPs and only used the last 1.5 of steady activity to measure the LFPs phase resetting induced by the brief 10 ms light stimulus. We found that the steady dynamics of mPFC in response to light stimuli could be reconstructed in a three-dimensional phase space with topologically similar ``8''-shaped attractors across different animals. Therefore, cocaine did not change the complexity of the recorded nonlinear data compared to the control case. The phase space of the reconstructed attractor is determined by the LFP time series and its temporally shifted versions by a multiple of some lag time. We also compared the change in the attractor shape between cocaine-injected and control using (1) dendrogram clustering and (2) Frechet distance. We found about 20% overlap between control and cocaine trials when classified using dendrogram method, which suggest that it may be possible to describe mathematically both data sets with the same model and slightly different model parameters. We also found that the lag times are about three times shorter for cocaine trials compared to control. As a result, although the bluephase space trajectories for control and cocaine bluemay look similar, their dynamics is significantly different.